THE UTILIZATION OF USED DRUMS AS TRASH CANS IN BUENG VILLAGE, JANTHO ACEH BESAR - Syammaun, Tamalkhani; Rani, Hafnidar A.; Diwa, Lukmana Umara; Junaidi, Junaidi; Irawan, Yudi; Perdana, Nazar Iqbal (Universitas Muhammadiyah Aceh, 2021)
Garbage is goods derived from human activities that are no longer used, either unused or discarded. Good waste management not only makes the environment clean and healthy, but can also improve the community's economy. Bueng Village is one of the villages in the Jantho City District, Aceh Besar Regency which is classified as underdeveloped according to the Village Development Index and classified as underdeveloped according to the Village Development Index. The livelihoods of the people in Gampong Bueng are mostly farmers, because this village is located in the mountains and filled with rice fields. The problem that occurs in Bueng Village is that there is no garbage disposal area, so a lot of garbage is thrown carelessly around the location and causes an unpleasant odor. Therefore, there is a need for a garbage disposal site that can make it easier for the surrounding community to dispose of waste in its place. So the potential for used drums is very interesting to function as a high-value trash can both from an aesthetic and economical point of view. In addition to having the advantage of a strong base material, used drums have sufficient volume. The purpose of making this trash can is to minimize waste in Bueng Village. With the trash can, there will be public awareness to collect garbage and dispose of garbage in its place so that the environment is clean and free from disease.Keywords: Used drums, environment, garbage